Theory HyperNat

theory HyperNat
imports StarDef
(*  Title       : HyperNat.thy
Author : Jacques D. Fleuriot
Copyright : 1998 University of Cambridge

Converted to Isar and polished by lcp
*)


header{*Hypernatural numbers*}

theory HyperNat
imports StarDef
begin

type_synonym hypnat = "nat star"

abbreviation
hypnat_of_nat :: "nat => nat star" where
"hypnat_of_nat == star_of"

definition
hSuc :: "hypnat => hypnat" where
hSuc_def [transfer_unfold]: "hSuc = *f* Suc"

subsection{*Properties Transferred from Naturals*}

lemma hSuc_not_zero [iff]: "!!m. hSuc m ≠ 0"
by transfer (rule Suc_not_Zero)

lemma zero_not_hSuc [iff]: "!!m. 0 ≠ hSuc m"
by transfer (rule Zero_not_Suc)

lemma hSuc_hSuc_eq [iff]: "!!m n. (hSuc m = hSuc n) = (m = n)"
by transfer (rule nat.inject)

lemma zero_less_hSuc [iff]: "!!n. 0 < hSuc n"
by transfer (rule zero_less_Suc)

lemma hypnat_minus_zero [simp]: "!!z. z - z = (0::hypnat)"
by transfer (rule diff_self_eq_0)

lemma hypnat_diff_0_eq_0 [simp]: "!!n. (0::hypnat) - n = 0"
by transfer (rule diff_0_eq_0)

lemma hypnat_add_is_0 [iff]: "!!m n. (m+n = (0::hypnat)) = (m=0 & n=0)"
by transfer (rule add_is_0)

lemma hypnat_diff_diff_left: "!!i j k. (i::hypnat) - j - k = i - (j+k)"
by transfer (rule diff_diff_left)

lemma hypnat_diff_commute: "!!i j k. (i::hypnat) - j - k = i-k-j"
by transfer (rule diff_commute)

lemma hypnat_diff_add_inverse [simp]: "!!m n. ((n::hypnat) + m) - n = m"
by transfer (rule diff_add_inverse)

lemma hypnat_diff_add_inverse2 [simp]: "!!m n. ((m::hypnat) + n) - n = m"
by transfer (rule diff_add_inverse2)

lemma hypnat_diff_cancel [simp]: "!!k m n. ((k::hypnat) + m) - (k+n) = m - n"
by transfer (rule diff_cancel)

lemma hypnat_diff_cancel2 [simp]: "!!k m n. ((m::hypnat) + k) - (n+k) = m - n"
by transfer (rule diff_cancel2)

lemma hypnat_diff_add_0 [simp]: "!!m n. (n::hypnat) - (n+m) = (0::hypnat)"
by transfer (rule diff_add_0)

lemma hypnat_diff_mult_distrib: "!!k m n. ((m::hypnat) - n) * k = (m * k) - (n * k)"
by transfer (rule diff_mult_distrib)

lemma hypnat_diff_mult_distrib2: "!!k m n. (k::hypnat) * (m - n) = (k * m) - (k * n)"
by transfer (rule diff_mult_distrib2)

lemma hypnat_le_zero_cancel [iff]: "!!n. (n ≤ (0::hypnat)) = (n = 0)"
by transfer (rule le_0_eq)

lemma hypnat_mult_is_0 [simp]: "!!m n. (m*n = (0::hypnat)) = (m=0 | n=0)"
by transfer (rule mult_is_0)

lemma hypnat_diff_is_0_eq [simp]: "!!m n. ((m::hypnat) - n = 0) = (m ≤ n)"
by transfer (rule diff_is_0_eq)

lemma hypnat_not_less0 [iff]: "!!n. ~ n < (0::hypnat)"
by transfer (rule not_less0)

lemma hypnat_less_one [iff]:
"!!n. (n < (1::hypnat)) = (n=0)"
by transfer (rule less_one)

lemma hypnat_add_diff_inverse: "!!m n. ~ m<n ==> n+(m-n) = (m::hypnat)"
by transfer (rule add_diff_inverse)

lemma hypnat_le_add_diff_inverse [simp]: "!!m n. n ≤ m ==> n+(m-n) = (m::hypnat)"
by transfer (rule le_add_diff_inverse)

lemma hypnat_le_add_diff_inverse2 [simp]: "!!m n. n≤m ==> (m-n)+n = (m::hypnat)"
by transfer (rule le_add_diff_inverse2)

declare hypnat_le_add_diff_inverse2 [OF order_less_imp_le]

lemma hypnat_le0 [iff]: "!!n. (0::hypnat) ≤ n"
by transfer (rule le0)

lemma hypnat_le_add1 [simp]: "!!x n. (x::hypnat) ≤ x + n"
by transfer (rule le_add1)

lemma hypnat_add_self_le [simp]: "!!x n. (x::hypnat) ≤ n + x"
by transfer (rule le_add2)

lemma hypnat_add_one_self_less [simp]: "(x::hypnat) < x + (1::hypnat)"
by (insert add_strict_left_mono [OF zero_less_one], auto)

lemma hypnat_neq0_conv [iff]: "!!n. (n ≠ 0) = (0 < (n::hypnat))"
by transfer (rule neq0_conv)

lemma hypnat_gt_zero_iff: "((0::hypnat) < n) = ((1::hypnat) ≤ n)"
by (auto simp add: linorder_not_less [symmetric])

lemma hypnat_gt_zero_iff2: "(0 < n) = (∃m. n = m + (1::hypnat))"
apply safe
apply (rule_tac x = "n - (1::hypnat) " in exI)
apply (simp add: hypnat_gt_zero_iff)
apply (insert add_le_less_mono [OF _ zero_less_one, of 0], auto)
done

lemma hypnat_add_self_not_less: "~ (x + y < (x::hypnat))"
by (simp add: linorder_not_le [symmetric] add_commute [of x])

lemma hypnat_diff_split:
"P(a - b::hypnat) = ((a<b --> P 0) & (ALL d. a = b + d --> P d))"
-- {* elimination of @{text -} on @{text hypnat} *}
proof (cases "a<b" rule: case_split)
case True
thus ?thesis
by (auto simp add: hypnat_add_self_not_less order_less_imp_le
hypnat_diff_is_0_eq [THEN iffD2])
next
case False
thus ?thesis
by (auto simp add: linorder_not_less dest: order_le_less_trans)
qed

subsection{*Properties of the set of embedded natural numbers*}

lemma of_nat_eq_star_of [simp]: "of_nat = star_of"
proof
fix n :: nat
show "of_nat n = star_of n" by transfer simp
qed

lemma Nats_eq_Standard: "(Nats :: nat star set) = Standard"
by (auto simp add: Nats_def Standard_def)

lemma hypnat_of_nat_mem_Nats [simp]: "hypnat_of_nat n ∈ Nats"
by (simp add: Nats_eq_Standard)

lemma hypnat_of_nat_one [simp]: "hypnat_of_nat (Suc 0) = (1::hypnat)"
by transfer simp

lemma hypnat_of_nat_Suc [simp]:
"hypnat_of_nat (Suc n) = hypnat_of_nat n + (1::hypnat)"
by transfer simp

lemma of_nat_eq_add [rule_format]:
"∀d::hypnat. of_nat m = of_nat n + d --> d ∈ range of_nat"
apply (induct n)
apply (auto simp add: add_assoc)
apply (case_tac x)
apply (auto simp add: add_commute [of 1])
done

lemma Nats_diff [simp]: "[|a ∈ Nats; b ∈ Nats|] ==> (a-b :: hypnat) ∈ Nats"
by (simp add: Nats_eq_Standard)


subsection{*Infinite Hypernatural Numbers -- @{term HNatInfinite}*}

definition
(* the set of infinite hypernatural numbers *)
HNatInfinite :: "hypnat set" where
"HNatInfinite = {n. n ∉ Nats}"

lemma Nats_not_HNatInfinite_iff: "(x ∈ Nats) = (x ∉ HNatInfinite)"
by (simp add: HNatInfinite_def)

lemma HNatInfinite_not_Nats_iff: "(x ∈ HNatInfinite) = (x ∉ Nats)"
by (simp add: HNatInfinite_def)

lemma star_of_neq_HNatInfinite: "N ∈ HNatInfinite ==> star_of n ≠ N"
by (auto simp add: HNatInfinite_def Nats_eq_Standard)

lemma star_of_Suc_lessI:
"!!N. [|star_of n < N; star_of (Suc n) ≠ N|] ==> star_of (Suc n) < N"
by transfer (rule Suc_lessI)

lemma star_of_less_HNatInfinite:
assumes N: "N ∈ HNatInfinite"
shows "star_of n < N"
proof (induct n)
case 0
from N have "star_of 0 ≠ N" by (rule star_of_neq_HNatInfinite)
thus "star_of 0 < N" by simp
next
case (Suc n)
from N have "star_of (Suc n) ≠ N" by (rule star_of_neq_HNatInfinite)
with Suc show "star_of (Suc n) < N" by (rule star_of_Suc_lessI)
qed

lemma star_of_le_HNatInfinite: "N ∈ HNatInfinite ==> star_of n ≤ N"
by (rule star_of_less_HNatInfinite [THEN order_less_imp_le])

subsubsection {* Closure Rules *}

lemma Nats_less_HNatInfinite: "[|x ∈ Nats; y ∈ HNatInfinite|] ==> x < y"
by (auto simp add: Nats_def star_of_less_HNatInfinite)

lemma Nats_le_HNatInfinite: "[|x ∈ Nats; y ∈ HNatInfinite|] ==> x ≤ y"
by (rule Nats_less_HNatInfinite [THEN order_less_imp_le])

lemma zero_less_HNatInfinite: "x ∈ HNatInfinite ==> 0 < x"
by (simp add: Nats_less_HNatInfinite)

lemma one_less_HNatInfinite: "x ∈ HNatInfinite ==> 1 < x"
by (simp add: Nats_less_HNatInfinite)

lemma one_le_HNatInfinite: "x ∈ HNatInfinite ==> 1 ≤ x"
by (simp add: Nats_le_HNatInfinite)

lemma zero_not_mem_HNatInfinite [simp]: "0 ∉ HNatInfinite"
by (simp add: HNatInfinite_def)

lemma Nats_downward_closed:
"[|x ∈ Nats; (y::hypnat) ≤ x|] ==> y ∈ Nats"
apply (simp only: linorder_not_less [symmetric])
apply (erule contrapos_np)
apply (drule HNatInfinite_not_Nats_iff [THEN iffD2])
apply (erule (1) Nats_less_HNatInfinite)
done

lemma HNatInfinite_upward_closed:
"[|x ∈ HNatInfinite; x ≤ y|] ==> y ∈ HNatInfinite"
apply (simp only: HNatInfinite_not_Nats_iff)
apply (erule contrapos_nn)
apply (erule (1) Nats_downward_closed)
done

lemma HNatInfinite_add: "x ∈ HNatInfinite ==> x + y ∈ HNatInfinite"
apply (erule HNatInfinite_upward_closed)
apply (rule hypnat_le_add1)
done

lemma HNatInfinite_add_one: "x ∈ HNatInfinite ==> x + 1 ∈ HNatInfinite"
by (rule HNatInfinite_add)

lemma HNatInfinite_diff:
"[|x ∈ HNatInfinite; y ∈ Nats|] ==> x - y ∈ HNatInfinite"
apply (frule (1) Nats_le_HNatInfinite)
apply (simp only: HNatInfinite_not_Nats_iff)
apply (erule contrapos_nn)
apply (drule (1) Nats_add, simp)
done

lemma HNatInfinite_is_Suc: "x ∈ HNatInfinite ==> ∃y. x = y + (1::hypnat)"
apply (rule_tac x = "x - (1::hypnat) " in exI)
apply (simp add: Nats_le_HNatInfinite)
done


subsection{*Existence of an infinite hypernatural number*}

definition
(* omega is in fact an infinite hypernatural number = [<1,2,3,...>] *)
whn :: hypnat where
hypnat_omega_def: "whn = star_n (%n::nat. n)"

lemma hypnat_of_nat_neq_whn: "hypnat_of_nat n ≠ whn"
by (simp add: hypnat_omega_def star_of_def star_n_eq_iff)

lemma whn_neq_hypnat_of_nat: "whn ≠ hypnat_of_nat n"
by (simp add: hypnat_omega_def star_of_def star_n_eq_iff)

lemma whn_not_Nats [simp]: "whn ∉ Nats"
by (simp add: Nats_def image_def whn_neq_hypnat_of_nat)

lemma HNatInfinite_whn [simp]: "whn ∈ HNatInfinite"
by (simp add: HNatInfinite_def)

lemma lemma_unbounded_set [simp]: "{n::nat. m < n} ∈ FreeUltrafilterNat"
apply (insert finite_atMost [of m])
apply (drule FreeUltrafilterNat.finite)
apply (drule FreeUltrafilterNat.not_memD)
apply (simp add: Collect_neg_eq [symmetric] linorder_not_le atMost_def)
done

lemma Compl_Collect_le: "- {n::nat. N ≤ n} = {n. n < N}"
by (simp add: Collect_neg_eq [symmetric] linorder_not_le)

lemma hypnat_of_nat_eq:
"hypnat_of_nat m = star_n (%n::nat. m)"
by (simp add: star_of_def)

lemma SHNat_eq: "Nats = {n. ∃N. n = hypnat_of_nat N}"
by (simp add: Nats_def image_def)

lemma Nats_less_whn: "n ∈ Nats ==> n < whn"
by (simp add: Nats_less_HNatInfinite)

lemma Nats_le_whn: "n ∈ Nats ==> n ≤ whn"
by (simp add: Nats_le_HNatInfinite)

lemma hypnat_of_nat_less_whn [simp]: "hypnat_of_nat n < whn"
by (simp add: Nats_less_whn)

lemma hypnat_of_nat_le_whn [simp]: "hypnat_of_nat n ≤ whn"
by (simp add: Nats_le_whn)

lemma hypnat_zero_less_hypnat_omega [simp]: "0 < whn"
by (simp add: Nats_less_whn)

lemma hypnat_one_less_hypnat_omega [simp]: "1 < whn"
by (simp add: Nats_less_whn)


subsubsection{*Alternative characterization of the set of infinite hypernaturals*}

text{* @{term "HNatInfinite = {N. ∀n ∈ Nats. n < N}"}*}

(*??delete? similar reasoning in hypnat_omega_gt_SHNat above*)
lemma HNatInfinite_FreeUltrafilterNat_lemma:
assumes "∀N::nat. {n. f n ≠ N} ∈ FreeUltrafilterNat"
shows "{n. N < f n} ∈ FreeUltrafilterNat"
apply (induct N)
using assms
apply (drule_tac x = 0 in spec, simp)
using assms
apply (drule_tac x = "Suc N" in spec)
apply (elim ultra, auto)
done

lemma HNatInfinite_iff: "HNatInfinite = {N. ∀n ∈ Nats. n < N}"
apply (safe intro!: Nats_less_HNatInfinite)
apply (auto simp add: HNatInfinite_def)
done


subsubsection{*Alternative Characterization of @{term HNatInfinite} using
Free Ultrafilter*}


lemma HNatInfinite_FreeUltrafilterNat:
"star_n X ∈ HNatInfinite ==> ∀u. {n. u < X n}: FreeUltrafilterNat"
apply (auto simp add: HNatInfinite_iff SHNat_eq)
apply (drule_tac x="star_of u" in spec, simp)
apply (simp add: star_of_def star_less_def starP2_star_n)
done

lemma FreeUltrafilterNat_HNatInfinite:
"∀u. {n. u < X n}: FreeUltrafilterNat ==> star_n X ∈ HNatInfinite"
by (auto simp add: star_less_def starP2_star_n HNatInfinite_iff SHNat_eq hypnat_of_nat_eq)

lemma HNatInfinite_FreeUltrafilterNat_iff:
"(star_n X ∈ HNatInfinite) = (∀u. {n. u < X n}: FreeUltrafilterNat)"
by (rule iffI [OF HNatInfinite_FreeUltrafilterNat
FreeUltrafilterNat_HNatInfinite])

subsection {* Embedding of the Hypernaturals into other types *}

definition
of_hypnat :: "hypnat => 'a::semiring_1_cancel star" where
of_hypnat_def [transfer_unfold]: "of_hypnat = *f* of_nat"

lemma of_hypnat_0 [simp]: "of_hypnat 0 = 0"
by transfer (rule of_nat_0)

lemma of_hypnat_1 [simp]: "of_hypnat 1 = 1"
by transfer (rule of_nat_1)

lemma of_hypnat_hSuc: "!!m. of_hypnat (hSuc m) = 1 + of_hypnat m"
by transfer (rule of_nat_Suc)

lemma of_hypnat_add [simp]:
"!!m n. of_hypnat (m + n) = of_hypnat m + of_hypnat n"
by transfer (rule of_nat_add)

lemma of_hypnat_mult [simp]:
"!!m n. of_hypnat (m * n) = of_hypnat m * of_hypnat n"
by transfer (rule of_nat_mult)

lemma of_hypnat_less_iff [simp]:
"!!m n. (of_hypnat m < (of_hypnat n::'a::linordered_semidom star)) = (m < n)"
by transfer (rule of_nat_less_iff)

lemma of_hypnat_0_less_iff [simp]:
"!!n. (0 < (of_hypnat n::'a::linordered_semidom star)) = (0 < n)"
by transfer (rule of_nat_0_less_iff)

lemma of_hypnat_less_0_iff [simp]:
"!!m. ¬ (of_hypnat m::'a::linordered_semidom star) < 0"
by transfer (rule of_nat_less_0_iff)

lemma of_hypnat_le_iff [simp]:
"!!m n. (of_hypnat m ≤ (of_hypnat n::'a::linordered_semidom star)) = (m ≤ n)"
by transfer (rule of_nat_le_iff)

lemma of_hypnat_0_le_iff [simp]:
"!!n. 0 ≤ (of_hypnat n::'a::linordered_semidom star)"
by transfer (rule of_nat_0_le_iff)

lemma of_hypnat_le_0_iff [simp]:
"!!m. ((of_hypnat m::'a::linordered_semidom star) ≤ 0) = (m = 0)"
by transfer (rule of_nat_le_0_iff)

lemma of_hypnat_eq_iff [simp]:
"!!m n. (of_hypnat m = (of_hypnat n::'a::linordered_semidom star)) = (m = n)"
by transfer (rule of_nat_eq_iff)

lemma of_hypnat_eq_0_iff [simp]:
"!!m. ((of_hypnat m::'a::linordered_semidom star) = 0) = (m = 0)"
by transfer (rule of_nat_eq_0_iff)

lemma HNatInfinite_of_hypnat_gt_zero:
"N ∈ HNatInfinite ==> (0::'a::linordered_semidom star) < of_hypnat N"
by (rule ccontr, simp add: linorder_not_less)

end